Genetic background of calcium and phosphorus phases predicted from milk mid-infrared spectra of Holstein cows. Issue 1 (1st January 2021) - Franzoi, Marco; Costa, Angela; Penasa, Mauro; De Marchi, Massimo
Abstract: In bovine milk, Ca and P are partitioned between micellar (MP) and soluble phase (SP), both having important effects on coagulation properties. In particular, greater mineral content in the MP translates into better milk coagulation ability. Nevertheless, the high analytic costs of gold standard methods hamper the possibility to deepen partition of minerals in MP and SP on a large scale. In this study, MP and SP of Ca and P were predicted from 111, 653 milk mid-infrared spectra of Holstein cows to investigate genetic parameters. The average coefficient of determination of the prediction models in cross validation was 0.73. Heritability estimates of MP and SP of Ca and P ranged from 0.472 to 0.548 and the two phases of the same mineral were negatively correlated. The MP of Ca was genetically associated with protein yield (0.284) and content (0.658); in the case of MP of P, the latter were equal to 0.262 and 0.808, respectively. The current selection index of Italian Holstein places positive emphasis on protein percentage and yield, thus it is likely that the MP of the investigated minerals is increasing at the expense of the SP. In perspective, it would be important to assess genetic correlations between measured and predicted phenotypes to corroborate the use of such predictions for management and breeding purposes. Highlights: Micellar and soluble fractions of Ca and P predicted from milk spectra are heritable. Micellar fraction of Ca and P is favourably genetically associated with traits of interest for the dairy industry, such as milk protein and coagulation properties. The Italian Holstein selection index emphasises protein percentage and yield, and thus it is indirectly improving micellar phase of Ca and P.